Advanced Design Cultures: Long-Term Perspective and Continuous Innovation - Celi, Manuela (Springer, 2015)
This book describes new thinking and practice in Advanced Design (ADD) – design that is not merely highly developed but anticipates the future by envisioning novel products and processes. The focus is especially on the front end of innovation and the search for solutions in complex pioneering processes using design-related tools and practices. The book opens by describing these tools, the approaches that characterize ADD and its historical dimension. Specific fields in which ADD has flourished are then examined, exploring the dynamics between research and design. The coverage ranges from transportation, lighting and electrical appliances through to business networks, technology parks and the development of ground-breaking materials. Advance Design is the name of the research group at the Politecnico di Milano (Italy’s largest technical university) of which the authors are members. It was chosen to reflect both the “advanced”, tangible dimension of design in terms of modern product development, materials and technologies and an orientation toward radical innovation through user involvement and imagination.